Intrauterine growth restriction associated with excessively long umbilical cord: a case report and literature review. - Ann Schmid; Yves Jacquemyn; Jeannette De Loor (Clinics and Practice, 2013)
We present a 37-week female baby, known with intrauterine growth restriction since 25 weeks of pregnancy, born with a placenta with an excessive long umbilical cord (ELUC), without any other abnormalities. ELUC is mostly an incidental finding after delivery, but represents a potentially detectable intrauterine cause of growth restriction. A system that allows ultrasound measurement of the length of the umbilical cord could highly increase antenatal diagnosis of ELUC.